Pengembangan Game Educative Berbasis Android pada Materi Bangun Ruang untuk Siswa Sekolah Dasar - Muhammad Trio Maulana Putra; Ariesta Kartika Sari; Medika Risnasari (Universitas Trunojoyo Madura, 2018)
The aim of this study is to develop learning media for Android-based educative games on solid figures for students of elementary school. The game developed aims to facilitate students at the elementary school level to learn well. With develop this media, it is expected that students in elementary schools do not feel bored in following mathematics learning because they can learn while playing. The research method used is the 4D model namely Define, Design, Development, and Dissemination. the steps of 4D model are adopted from Thiagarajan (Sugiyono, 2016) as follows: (1) Define: contains activities to determine what products will be developed and the specification of products. in this steps, the researcher doing analysis about initial conditions through literature studies, (2) Design: containing activities to design a predetermined product. (3) Development: contains activities to make designs into products repeatedly until the Android-based educative games according to predetermined criteria. (4) Dissemination (Dissemination), containing activities to disseminate products that have been tested to be used by others. However, this research is only limited to step 3, namely the Development stage.